Thoth 2.0: evolução de uma ferramenta para a condução de revisões sistemáticas da literatura - (:unkn) unknown (Universidade Federal do Pampa, 2026)
Background - Systematic Literature Reviews (SLRs) are widely used to identify, analyze, and synthesize research studies within a specific domain, enabling the identification of research trends and underexplored gaps. However, conducting an SLR manually is a time-consuming and demanding process that requires significant effort and careful attention from researchers. Additionally, existing supporting tools often present limitations related to usability, integration of functionalities, and continuous maintenance. In this context, the previous version of the Thoth tool also exhibited technical issues, technological obsolescence, and lack of sustained evolution, motivating the development of a new version. Objective - To develop and evaluate a new version of the Thoth tool with the aim of supporting the systematic and collaborative conduction of systematic literature reviews, incorporating structural improvements, new functionalities, and support for the Snowballing method. Method - This research adopts an empirical, artifact-oriented approach grounded in the principles of Design Science Research (DSR). Initially, a Systematic Mapping Study (SMS) was conducted to identify existing tools and their limitations. Subsequently, a complementary survey was carried out to understand researchers practices, challenges, and needs when conducting SLRs and applying the Snowballing method. Based on these empirical findings, the new version of the tool was designed and implemented. Finally, the proposed solution was evaluated through a usability evaluation, considering users perceptions regarding usefulness, ease of use, and overall experience. Results - The findings from the SMS and the survey supported the definition of requirements and functionalities incorporated into the new version of Thoth. The usability evaluation enabled the identification of positive aspects related to perceived usefulness and ease of use, as well as limitations and opportunities for improvement, leading to refinements in the interface, user experience, and support for managing the systematic review process. Conclusion - The results indicate that, although several tools exist to support SLRs and the Snowballing method, limitations remain regarding integrated support for process management. The new version of the Thoth tool contributes by proposing an empirically grounded solution that provides systematic support for different stages of the literature review process and for the Snowballing method, while also establishing an architectural foundation oriented toward continuous evolution and maintenance.
Keywords: Engenharia de software; Ferramentas de busca na Web; Thoth; Plataformas colaborativas; Revisões sistemáticas de literatura; Software engineering; Web search tools; Collaborative platforms; Systematic literature review; CIENCIAS EXATAS E DA TERRA